Pengaruh Integritas, Kompetensi, Dan Disiplin Kerja Terhadap Kinerja Pegawai Kantor Pengawasan Dan Pelayanan Bea Dan Cukai (KPPBC) Tipe Madya Pabean Tanjung Emas Semarang - Frenky Mangasa; Sutopo Sutopo (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2023)
This study aims to determine the effect of integrity, competence, and work discipline on the performance of employees of the Kantor Pengawasan Dan Pelayanan Bea Dan Cukai (KPPBC)Tipe Madya Pabean Tanjung Emas Semarang. The research population included all employees of the Office KPPBC Type Madya Tanjung Emas Semarang, totaling 205 people and 67 people were taken as a sample. The analysis technique uses multiple linear regression statistical methods. The results showed: Integrity, Competence, and Work Discipline simultaneously have a significant effect on Employee Performance. Partially, integrity has a significant positive effect on employee performance, competence has a significant positive effect on employee performance and work discipline has a significant positive effect on employee performance.